Study On Influence Of Moisture Content In Cement Stabilized Serian Soil - Siti Nor Linda, Binti Taib; Striprabu, Strimari; Fauziah, Binti Ahmad; Foo, Kelvin Chin Yen; Khor, Brandon Ling Seong (Construction Research Institute of Malaysia (CREAM), 2018)
The aim of the study is to investigate the strength development of cement stabilized Serian soil at varying moisture content. The soil sample was mixed with 10 % of cement by dry weight of soil and added with different percentage of water to replicate field site conditions. The water content used were the lower limit of Optimum Moisture Content (0.7 OMC), Optimum Moisture Content (OMC), and an upper limit of Optimum Moisture Content (1.27 OMC) which were 19.5%, 28%, and 35.5% respectively. Compaction test performed on the natural and cement stabilized soil. The Atterberg limits also were performed for natural soil and cement stabilized the soil. The Unconfined Compression Strength (UCS) was conducted to examine the effect of compressive strength. Consolidated Isotropic Undrained (CIU) Triaxial test with various confining pressures was conducted for cement stabilized soil. The Atterberg limits improved for stabilized soil compared to natural soil. The cement stabilized soil mixed 1.27 OMC achieved highest compressive strength and exhibit higher deviator stress from Triaxial test and followed with mixed at OMC and finally at 0.7 OMC. From Scanning Electron Microscopy (SEM) observation, cement stabilized soil had better intercluster cementation bonding and reduced pore spaces.